Case report: Mixed dementia associated with autoantibodies targeting the vesicular glutamate transporter 2 - Hansen, Niels; Teegen, Bianca; Hirschel, Sina; Wiltfang, Jens; Schott, Björn H.; Bartels, Claudia; Bouter, Caroline (Frontiers in Psychiatry, 2023)
Background Autoantibodies against the vesicular glutamate transporter type 2 (VGlut2) can trigger impaired synaptic signaling and are described here for the first time in association with mixed dementia. Methods We report on a 71-year-old female patient with a dementing syndrome who underwent a thorough dementia diagnosis including neuropsychological testing, magnetic resonance imaging (MRI), 18F-fluorodesoxyglucose positron emission tomography (FDG-PET), and a spinal tap to search for neural autoantibodies. Results Our patient exhibited mixed dementia. Her CSF revealed elevated ptau 181 protein and a reduced Aß42/40 ratio indicating Alzheimer's disease (AD) pathology. In addition, neuropsychological testing showed a profile consistent with AD with impaired memory, reduced semantic word fluency, naming disorder, and impaired visuoconstructive skills. Nevertheless, in-depth neuropsychological testing also revealed marked psychomotor slowing and visuospatial perceptual impairments that are more indicative of the presence of DLB. Overall, her dementia is more likely of mixed pathology. In addition, we repeatedly detected VGlut2 autoantibodies in her serum. Conclusion To the best of our knowledge, this report is the first to describe mixed dementia associated with VGlut2 autoantibodies.